﻿Review of the leafhopper tribe Deltocephalini Dallas, 1870 (Hemiptera, Cicadellidae, Deltocephalinae) in Pakistan with description of a new species of Paramesodes - Hassan Naveed; Bismillah Shah; Kamran Sohail; Yalin Zhang; Keping Chen (ZooKeys, 2023)
A review of the leafhopper tribe Deltocephalini in Pakistan is provided, including comprehensive illustrated keys to all genera and species, along with their diagnosis and distribution. A new species of Paramesodes is described, P. dirensis sp. nov., which was discovered in the Upper Dir District of Khyber Pakhtunkhwa, Pakistan. A detailed description of this new species is provided together with photographs for visual reference. This tribe now has three genera and 13 species from Pakistan. The genus Deltocephalus Burmeister includes two species, and Maiestas Distant has nine species; Paramesodes Ishihara is now represented with two species.